Fractional Exhaled Nitric Oxide Measurements and Screening of Obstructive Sleep Apnea in a Sleep-Laboratory Setting: A Cross-Sectional Study - Duarte, Ricardo L M (2019)
PURPOSE: Obstructive sleep apnea (OSA) is a common condition characterized by repetitive collapse of the upper airways and intermittent oxygen desaturation, which may lead to airway inflammation. Here, we explored whether fractional exhaled nitric oxide (FeNO) levels provide a non-invasive screening tool of OSA. METHODS: Over a 3-month period, FeNO levels were measured in consecutive non-smoking patients referred for a sleep laboratory. All patients underwent full polysomnography. OSA severity was classified based on the apnea/hypopnea index: ≥ 5.0/h as any OSA, ≥ 15.0/h as moderate/severe OSA, and ≥ 30.0/h as severe OSA. FeNO was measured by a portable device (NIOX-MINO®; Aerocrine AB, Solna, Sweden) and expressed as parts per billion (ppb). Discrimination by area under the curve (AUC) and binary logistic regression were performed. RESULTS: A total of 229 subjects were evaluated. Mean FeNO values were similar among subjects without OSA or with OSA: 16.9 ± 10.6 ppb versus 20.2 ± 14.5 ppb, p = 0.221; respectively. FeNO was not an inclusionary parameter to predict any OSA, moderate/severe OSA, and severe OSA: odds ratio (OR) 1.023 (95% confidence interval [CI]: 0.986-1.062); OR 1.012 (95% CI: 0.991-1.034); and OR 0.999 (95% CI: 0.980-1.018), respectively. The AUC values for FeNO in the diagnosis of any OSA, moderate/severe OSA, and severe OSA showed no discriminatory properties: AUC: 0.567 (95% CI: 0.464-0.670), AUC: 0.541 (95% CI: 0.465-0.618), and AUC: 0.535 (95% CI: 0.459-0.610); respectively. CONCLUSIONS: In a sleep-lab setting, our findings suggest that FeNO measurements are inconsequential in the screening of OSA in adults.